Status of robotic assistance: a less traumatic and more accurate minimally invasive surgery? - Kenngott, Hannes Götz; Fischer, Lars; Nickel, Felix; Rom, Joachim; Rassweiler, Jens; Müller, Beat P. (Langenbeck's archives of surgery, 2012)
PurposeRobotic assistance is considered one innovation within abdominal surgery over the past decade that has the potential to compensate for the drawbacks of conventional laparoscopy, such as limited degree of freedom, 2D vision, fulcrum, and pivoting effect. Robotic systems provide corresponding solutions as 3D view, intuitive motion and enable additional degrees of freedom. This review provides an overview of the history of medical robotics, experimental studies, clinical state-of-the-art and economic impact.MethodsThe Medline database was searched for the terms “robot*, telemanipulat*, and laparoscop*.” A total of 2573 references were found. All references were considered for information on robotic assistance in advanced laparoscopy. Further references were obtained through cross-referencing the bibliography cited in each work.ResultsIn experimental studies, current robotic systems showed superior handling and ergonomics compared to conventional laparoscopic techniques. In gynecology especially for hysterectomy and in urology especially for prostatectomy, two procedures formerly performed via an open approach, the robot enables a laparoscopic approach. This results in reduced need for pain medication, less blood loss, and shorter hospital stay. Within abdominal surgery, clinical studies were generally unable to prove a benefit of the robot. While the benefit still remains open to discussion, robotic systems are spreading and are available worldwide in tertiary centers.ConclusionRobotic assistance will remain an intensively discussed subject since clinical benefits for most procedures have not yet been proven. The most promising procedures are those in which the robot enables a laparoscopic approach where open surgery is usually required.